Potencial de linhagens de feijão vermelho no Campo das Vertentes de Minas Gerais - Jeque, Domingos Armando Soquir (2023)
The common bean (Phaseolus vulgaris L.) has great socioeconomic importance in Brazil. This species presents a great diversity of commercial types, of which the carioca and black beans are the most consumed in Brazil. However, there are other types of grains that are regionally important, such as red beans, widely cultivated in the Zona da Mata Mineira. Despite the growing demand for red bean in the mesoregions of Zona da Mata and Campos das Vertentes in Minas Gerais, there are few initiatives in breeding programs aimed at obtaining cultivars with this type of bean. Therefore, the UFLA and UFV bean breeding programs play an important role in recommending cultivars with these types of grains for Minas Gerias. This work aimed to evaluate the performance of red bean lines in order to identify potential parents to compose crosses and future tests of VCU. Forty-eight red bean lineages originating from UFV and CIAT were evaluated in experiments carried out in the 2020 and 2021 wet and autumn-winter harvests, in the 2022 drought at the Center for Scientific and Technological Development of the Federal University of Lavras. The experimental design for all experiments was randomized blocks with three replications. The evaluated characteristics were grain yield (kg.ha-1), grain appearance, plant architecture and severity of bacterial blight. Individual and joint analyzes of variance were performed for all characteristics and the Scott-Knott mean grouping test was applied. The percentages of the complex part of the interaction between genotypes and pairs of environments and the Pearson correlations between pairs of environments were also quantified. In order to characterize the adaptability of the evaluated lines, the centroid method was used. Significant genotype-by-environment interactions were detected for all traits evaluated in the joint analysis of variance. The interaction between genotypes and environments was predominantly of a complex nature for the traits grain yield, bacterial blight severity and plant architecture, while for appearance of the grains it was of a simple nature. The BRSMG Marte, UFV5, CIAT2 and CIAT5 lines showed the potential to be used in blocks of crosses in red bean breeding programs because they showed high productive potential, good adaptability, grains with commercial acceptance and plants with erect architecture. Therefore, the strains UFV5, CIAT2 and CIAT5 have the potential to be included in trials of value for cultivation and use.